Implementation of the Kauny Quantum Memory Method in Fostering the Ability to Memorize the Qur'an at the Al Kautsar Cianjur Islamic Boarding School - Karimah, Rika Siti; Irawan, Irawan; Nasir, Tatang Muh (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The Kauny Quantum Memory method is a method of memorizing the Qur'an by offering alternative solutions for memorizing the Qur'an into an easy, practical and fun activity. The technique used is by optimizing the intelligence of the right brain to capture visualization of meaning, illustration of meaning, making up stories and associating verse by verse that has been memorized. The purpose of this study was to find out how to implement the Kauny Quantum Memory method in fostering the ability to memorize the Qur'an at the Al-Kautsar Cianjur Islamic boarding school. This study used a qualitative approach with qualitative descriptive research methods while the data collection process used observation, interviews, and documentation. Analysis in qualitative research is carried out during the research, and after collecting data for a certain time. The Al-Kautsar Islamic Boarding School was established under the auspices of the Talaga Expert Foundation as a form of concern for the quality of the Islamic generation. The steps for applying the Kauny Quantum Memory method when memorizing with body movements are as follows: first, when you want to memorize a letter using the Kauny method the first step that must be taken is to pay attention to the movements demonstrated by the teacher. For example, إذَا the movement is to raise the right hand while pointing up. The movement, الشَّمْسُ is to form a circle like the sun with two hands. Second, follow the movements given by the teacher and do it repeatedly. Third, then after memorizing the movements by knowing the meaning per word and per verse, the teacher gives an explanation about asbabun nuzul from the verse. Fourth, the students write down the memorized verses.